Interfacing biology with nanoparticles - Mandal, Sujata; Phadtare, S.; Sastry, M. (Current Applied Physics, 2005)
New approaches are constantly being developed for both the synthesis of inorganic nanomaterials and their surface modification for sensing and electronic applications. Insofar as surface modification of gold nanoparticles is concerned, thiol chemistry is the most popular approach to bind ligands to their surface. We have been pursuing the possibility of using amine functionality to bind ligands to the surface of gold nanoparticles and have found that amine binding is as strong as thiol binding. The advantages of using amine chemistry for surface modification of nanogold are many, the possibility of complexing a large variety of biomolecules such as amino acids and proteins being one of the most important. In this article, we review the work from this laboratory on the stabilization of gold nanoparticles using amino acids as well as using amino acids as reducing agents to obtain stable aqueous solutions of gold nanoparticles of variable size. We also discuss the possibility of forming bioconjugates of enzymes with gold nanoparticles decorating the surface of polymer microspheres and their application as reusable biocatalysts. There is much to be gained by marrying nanomaterials with biology with considerable spin-offs likely in both nanotechnology and biotechnology. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: amino acids' enzyme immobilization; Nanoparticles; Proteins

Keggin ion mediated synthesis of hydrophobized pd nanoparticles for multifunctional catalysis - Mandal, Sujata; Das, Amitava; Srivastava, R.; Sastry, M. (Langmuir, 2005)
Development of simple and reliable protocols for the synthesis of organically soluble catalytically active metal nanoparticles is an important aspect of research in nanomaterials. We demonstrate herein the formation of Pd nanoparticles by reduction of aqueous Pd(NO3)(2) by photoexcited Keggin ions (phosphotungstate anions). This results in the formation of Pd nanoparticles capped with with Keggin ions that render the particles negatively charged. The Keggin ion capped Pd nanoparticles may then be phase transferred into nonpolar organic solvents such as toluene by electrostatic complexation with cationic surfactants such as octadecylamine at the liquid-liquid interface. This results in a new class of catalyst wherein both the Pd core and Keggin ion shell may be used in a range of catalytic reactions leading to a truly multifunctional catalyst dispersible in organic solvents.

New approaches to the synthesis of anisotropic, core-shell and hollow metal nanostructures - Sastry, M.; Swami, A.; Mandal, Sujata; Selvakannan, P. R. (Journal of Materials Chemistry, 2005)
The synthesis of nanomaterials with control over size, shape and chemical composition continues to be a major challenge in nanoscience. The requirements of nanomaterial synthesis are becoming more sophisticated and, in addition to anisotropic structures, there is much excitement surrounding the development of recipes for the synthesis of core-shell and hollow nanostructures. Much of the motivation for research in this direction stems from the unusual optoelectronic and chemical properties exhibited by such nanostructures. In this article, we review the work from this laboratory on the synthesis of flat gold nanostructures at the air-water interface, either by confining the reductant or the precursor metal ions to the air-water interface. We also describe the synthesis of phase-pure core-shell nanoparticles by immobilizing UV- and pH-dependent reducing agents on the surface of the core nanoparticles as well as the synthesis of organically soluble hollow-shell nanostructures via transmetallation reactions.

Silver nanoparticles of variable morphology synthesized in aqueous foams as novel templates - Mandal, Sujata; Arumugam, S. K.; Pasricha, R.; Sastry, M. (Bulletin of Materials Science, 2005)
In this paper, we describe the synthesis of silver nanocrystals within aqueous foams as a template More specifically, we show that aqueous Ag+ ions may be electrostatically complexed with the anionic surfactants aerosol OT (sodium bis-2-ethylhexyl-sulfosuccinate, (AOT) and sodium dodecyl sulphate (SDS)) in a highly stable liquid foam. After drainage of the foam, the silver ions are reduced in situ by introducing sodium borohydride into the foam by capillary flow. This leads to the formation of silver nanoparticles of spherical, tape- and sheet-like morphology in the foam. The structure of the foam is extremely complex and presents reaction sites of different spatial extent. The differences in foam reaction-site geometry are believed to be responsible for the morphology variation in the silver nanoparticles observed. The silver nanoparticles are observed to be extremely stable in solution suggesting that the AOT or SDS molecules stabilize them. This approach appears promising for application in large-scale synthesis of nanoparticles and may be readily extended to other chemical compositions.
Keywords: Chemical synthesis; composites; foam; Intercalation; Nanoparticles

Synthesis and assembly of gold nanoparticles in quasi-linear lysine-keggin-ion colloidal particles - Sanyal, A.; Mandal, Sujata; Sastry, M. (Advanced Functional Materials, 2005)
The formation of fiber-like colloidal particles of the amino acid lysine complexed with Keggin ions is demonstrated. The lysine-phosphotungstic acid (PTA) colloidal particles act as excellent templates for the synthesis and assembly of gold nanoparticles wherein the lysine-PTA complex acts as a UV-switchable reducing agent for gold ions. This novel bio-organic-inorganic template shows excellent potential as a regulated nanoreactor for application in programmed nanoparticle synthesis and assembly in a single step.

Synthesis of hydroxyapatite crystals using amino acid-capped gold nanoparticles as a scaffold - Rautaray, D.; Mandal, Sujata; Sastry, M. (Langmuir, 2005)
Inorganic composites are of special interest for biomedical applications such as in dental and bone implants wherein the ability to modulate the morphology and size of the inorganic crystals is important. One interesting possibility to control the size of inorganic crystals is to grow them on nanoparticles. We report here the use of surface-modified gold nanoparticles as templates for the growth of hydroxyapatite crystals. Crystal growth is promoted by a monolayer of aspartic acid bound to the surface of the gold nanoparticles; the carboxylate ions in aspartic acid are excellent hinging sites for Ca2+ ions. Isothermal titration calorimetry studies of Ca2+ ion binding with aspartic acid-capped gold nanoparticles indicates that the process is entropically driven and that screening of the negative charge by the metal ions leads to their aggregation. The aggregates of gold nanopartictes are believed to be responsible for assembly of the platelike hydroxyapatite crystals into quasi-spherical superstructures. Control experiments using uncapped gold nanoparticles and pure aspartic acid indicate that the amino acid bound to the nanogold surface plays a key role in inducing and directing hydroxyapatite crystal growth.

Adsorption of fluoride ions by Zn-Al layered double hydroxides - Mandal, Sujata; Mayadevi, S. (Applied Clay Science, 2008)
Zn-Al layered double hydroxides (LDHs) with different molar ratios Zn/Al (0, 0.17, 0.34, 0.97, 3.47, proportional to) were prepared by the co-precipitation of chlorides, characterized and evaluated for their fluoride adsorption at room temperature from aqueous solutions. The fluoride adsorption of the as-synthesized LDHs was influenced by the chemical composition of the LDHs and ZA-11 (Zn/Al = 0.97) had the highest capacity for fluoride adsorption (1.14-4.16 mg/g). The adsorption increased after calcination of the LDH up to 500 degrees C. The equilibrium data were fitted to the Freundlich, Langmuir, and Temkin equations. The kinetics of fluoride adsorption followed the pseudo-second order model. (C) 2007 Elsevier B.V All rights reserved.
Keywords: Adsorption; Anionic clay; Fluoride; Layered double hydroxide

Cellulose supported layered double hydroxides for the adsorption of fluoride from aqueous solution - Mandal, Sujata; Mayadevi, S. (Chemosphere, 2008)
Cellulose supported layered double hydroxides (CSLDHs) were synthesized and tested for adsorption of fluoride in aqueous medium. Three samples of cellulose supported LDHs were synthesized by varying the LDH loading on cellulose. The raw cellulose, unsupported LDH and cellulose supported LDHs were characterized by XRD, SEM and BET surface area. Batch adsorption as well as fixed-bed column experiments were performed for determining the fluoride adsorption characteristics of CSLDHs. The fluoride adsorption properties of CSLDHs were found to be superior to that of reported adsorbents, including activated alumina and carbon nanotubes. Defluoridation capacity of the CSLDHs was 2-4 times higher than that of unsupported LDH. The cellulose supported LDH, CSLDH-50, having an LDH loading of 27% showed maximum fluoride uptake capacity (5.29 mg g(-1) of CSLDH, 25.18 mg g(-1) of LDH) in fixed-bed column study. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; cellulose; Fluoride; Layered double hydroxide

Adsorption of aqueous selenite [Se(IV)] species on synthetic layered double hydroxide materials - Mandal, Sujata; Mayadevi, S.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2009)
{Layered double hydroxide materials (Zn/Al, Mg/Al, Zn/Fe) with varying composition (M(2+):M(3+) molar ratio

Azoic dye hosted in layered double hydroxide: physicochemical characterization of the intercalated materials - Mandal, Sujata; Tichit, Didier; Lerner, Dan A.; Marcotte, Nathalie (Langmuir, 2009)
Intercalation compounds were obtained by introduction of guest methyl orange (MO) into the interlayer space of host Mg/Al and Ni/Al layered double hydroxides (LDHs). Three synthesis methods of organic anion-LDH intercalation compounds, i.e., coprecipitation, reconstruction of the M(II)(Al)O mixed oxides, and anion exchange of LDH were compared. The former Method gives rise to a highly organized MO-intercalated Mg/Al LDH with an interlayer spacing of 2.43 rim and up to seven (001) reflection orders. Reconstruction or the mixed oxide by intercalation with MO in the restored LDH was only achieved with Mg(Al)O. In this case. a competitive adsorption of MO on the external Surface Of the crystals was also seen. On the other hand, intercalation compounds exhibiting interlayer spacing of 2.43 run were obtained with both Mg- and Ni-containing LDH using the anionic exchange method. The equilibrium and kinetic adsorption properties of the compounds were analyzed by UV-visible spectroscopy in anionic exchange experiments. According to the pseudo-second-order adsorption model, the amounts of adsorbed MO reach 3.82 and 2.83 mequiv/g for Mg- and Ni-containing LDHs, respectively, which are close to their respective anionic exchange capacity. The adsorption rates are on the same order of magnitude for the two LDHs (0.10-0.44 g mmol(-1) min(-1)), the equilibrium being reached in less than 60 min. The decomposition of MO by combustion of the organic moieties under an oxidizing atmosphere is delayed in Mg-containing MO-LDH hybrids when compared to the free MO molecule, showing that the thermal stability of MO species is enhanced after intercalation. In Ni-containing LDH, the main decomposition step of MO occurs 300 degrees C below that of Mg-containing LDH. This was rationalized in terms of a catalysis by the Ni-containing oxides formed during the thermal treatment. So these materials exhibit several advantage useful for the development of eco-friendly processes for the removal Of dyes from effluents of textile, plastic, and paper industries.

Defluoridation of water using as-synthesized Zn/Al/Cl anionic clay adsorbent: equilibrium and regeneration studies - Mandal, Sujata; Mayadevi, S. (Journal of Hazardous Materials, 2009)
Zn/Al/Cl anionic clay has been synthesized by co-precipitation method and applied for adsorption of fluoride in aqueous medium. Equilibrium adsorption data were fitted to Langmuir, Freundlich, Temkin, and Generalized isotherm equations. Thermodynamic parameters like Delta G and Delta H values show the feasibility and exothermic nature of the adsorption process. Influence of solution pH and presence of other anions on fluoride adsorption by the clay has also been studied. Presence of carbonate in water was found to have an adverse effect on fluoride adsorption by the clay. pH(pzc) of the clay has been found to be 8.97. A two-step 1st order kinetic model was used to explain the fluoride adsorption kinetics of the as-synthesized clay. It was possible to regenerate the adsorbent with an aqueous solution of 0.01 M NaOH and the effect of regeneration on fluoride adsorption was reported up to five regeneration cycles. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Anionic clay; Fluoride; Isotherm; kinetics; Regeneration

Structural characterization of azoic dye hosted layered double hydroxides - Mandal, Sujata; Lerner, Dan A.; Marcotte, Nathalie; Tichit, Didier (Zeitschrift fur Kristallographie, 2009)
The removal of methyl orange (MO) from an aqueous solution was performed using layered double hydroxides (LDHs) in a move to develop cleaning processes of effluents contaminated with dye molecules. The intercalation of the guest anionic MO species into host M(II)/Al(III) LDHs differing by the nature of the divalent cations (M(II) = Mg, Ni or Zn) was achieved by anionic exchange of the initially NO(3)(-) present in the interlayer space and led to MO/LDH intercalation compounds. The exchange process was followed by XRD and UV-visible absorption spectroscopy at different stages. Almost all MO in solution is uptaken by the Mg-containing LDH in the concentration range corresponding to its anionic exchange capacity (AEC). A lower exchange is reached with the Ni- and Zn-containing LDHs, for which the diffusion of MO is limited due to a larger crystallite size. MO-Zn/Al LDH intercalation compounds exhibit the highest crystallinity and display a remarkable stacking of the layers at maximal MO exchange. This behaviour can be assigned to the higher intrinsic charge density of the host layers in agreement with its lower M(II)/Al(III) molar ratio (Zn(II)/Al(III) approximate to 1.5 whereas Mg(II)/Al(III) and Ni(II)/Al(III) = 2). The maximum amount of MO retained by the different LDHs is higher for Mg-containing LDH, than for Ni- and Zn-containing LDH, reaching respectively 1.15, 0.84 and 0.77 g/g.
Keywords: Anionic exchange; Depollution; layered double hydroxides; Methyl orange; X-ray diffraction

Adsorption of cresols on zinc-aluminium hydroxides - a comparison with zeolite-X - Vijayakumar, J.; Chikkala, Suresh K.; Mandal, Sujata; Mayadevi, S. (Separation Science and Technology, 2011)
Liquid phase adsorption of m-cresol on Zn-Al hydroxide adsorbents with three different Zn/Al molar ratios was studied in different solvents and compared with commercial zeolite 13X. Among the three adsorbents, ZA-16 showed adsorption capacity similar to commercial zeolite 13X. Solvents used for the preparation of m-cresol solution were found to influence the adsorption capacity. The adsorption capacity was maximum for the solution of m-cresol in n-hexane. Conventional Langmuir and Freundlich adsorption isotherm equations were used to explain the adsorption behavior. The kinetics of m-cresol adsorption followed the first-order Lagergren kinetic model. p-Cresol/m-cresol separation factor was the highest when toluene was used as the organic medium.
Keywords: Adsorption; cresol; zeolite; zinc-aluminium hydroxide

Fluoride contamination of water: origin, health effects and remediation methods - Mandal, Sujata; Mayadevi, S. (Fluoride, 2011)
Fluorine is the 13th most abundant element in the earth?s crust. It exists in trace amounts in ground water all over the world. Drinking water is the primary source through which fluoride enters the human body, especially in regions where fluoride concentrations in groundwater and/or surface water are high. It is estimated that more than 200 million people worldwide depend on drinking water with fluoride concentration exceeding the present World Health Organization (WHO) guideline (Maximum contaminant level of 1.5 mg/l). Fluoride bearing foodstuffs and fumes from burning of coal also significantly contribute to the daily intake of people in some regions. Prolonged consumption of excess fluoride may lead to different types of fluorosis (dental and skeletal) depending on the level and period of exposure. Presence of fluoride in drinking water above permissible level has been related to increased incidence of fluorosis among the people all over the world including China, India, Australia, Mexico, Argentina, Egypt and Kenya. In India, the problem of excessive fluoride in groundwater was first reported in 1937 in the state of Andhra Pradesh. More than 6 million people all over India are known to be seriously affected by fluorosis and another 62 million are exposed to it. The best choice for combating fluorosis is to have alternative source of water with low fluoride level. In absence of alternative source of water, defluoridation of excess fluoride in water is the only option. Different methods are available for defluoridation of water. But the selection of the appropriate method for achieving a sustainable solution to the fluorosis problem is very important. Defluoridation of drinking water by adsorption is the most simple and effective technology that can work in household as well as community level drinking water treatment. It is also the most widely studied method for defluoridation of water, as the fluoride concentration in groundwater is usually very low (10 mg/l). A wide variety of adsorbents have been explored for this purpose. Synthetic layered double hydroxides are comparatively new materials examined for the adsorption of fluorides and they exhibit good fluoride adsorption capacity. A discussion on various defluoridation methods, adsorbents for defluoridation and recent developments are presented in this chapter.

Alginate and hydrotalcite-like anionic clay composite systems: synthesis, characterization and application studies - Mandal, Sujata; Patil, Varsha S.; Mayadevi, S. (Microporous and Mesoporous Materials, 2012)
Hydrotalcite-like anionic clays (Zn/Al and Mg/Al) were intercalated with sodium alginate to form organic-inorganic composite adsorbents for water treatment applications. The synthesized composites were characterized using different characterization techniques viz. XRD, DRIFTS, SEM and surface area/porosity analysis. The adsorption potential of the alginate-clay composites was examined for removal of fluoride ions and Orange II dye from water by adsorption. Our studies revealed that these composites had high adsorption capacity for the adsorption of fluoride and Orange II dye from aqueous solutions. The adsorption capacity of the composites was considerably higher than that of either alginate or clay, used individually. The results indicated that these materials might be useful sorbents for groundwater purification/effluent treatment. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Alginate; Anionic clay; Composite; Fluoride; Orange II dye

Synthetic layered double hydroxide on biodegradable support: an efficient adsorbent for defluoridation of water - Mayadevi, S.; Kirandas, M. D.; Manilal, A. M.; Roshini, N.; Mandal, Sujata (Indian Journal of Chemical Technology, 2024)
Fluoride concentrations in drinking water above permissible levels and incidences of fluorosis among people have been reported from many parts of the world including India. Low-cost and biodegradable adsorbents are the preferred choice for the removal of fluoride from an aqueous medium. In the present study, zinc-aluminium layered double hydroxide (LDH) supported on sugarcane bagasse (raw and acid-treated) has been synthesized, characterized, and investigated for the defluoridation of water. The SEM micrographs of the supported adsorbents show good dispersion of the LDH particles on the support material. The defluoridation capacity of the LDH is enhanced by supporting it on bagasse. The adsorption capacity of supported adsorbents increased by 3-fold than the unsupported LDH adsorbent. The adsorption data have been well fitted to the Freundlich isotherm model indicating physical and multi-layer adsorption. The maximum fluoride adsorption capacity has been found to be 8.85 mg/g with 76.3% fluoride removal when the initial fluoride concentration is 11-12 mg/L. The pseudo-second-order kinetic model has been found suitable to explain the fluoride adsorption kinetics on the supported LDH adsorbents. The present study reveals that the bagasse-supported LDH adsorbent has a high potential for defluoridation of water.
Keywords: adsorption kinetics; Fluoride adsorption; Layered double hydroxide; Sugarcane bagasse